The ‘Bravo Mike Syndrome': private security culture and racial profiling in South Africa - Diphoorn, Tessa G. (Policing and society, 2017)
This article analyses how issues of race influence the occupational culture of the armed response sector, a particular part of the private security industry, in Durban, South Africa. In addition to analysing the racial hierarchy of the industry, this article examines the ‘Bravo Mike Syndrome' - Bravo Mike meaning black male in NATO phonetic alphabet code. The ‘Bravo Mike Syndrome' refers to the racialised imaginaries of criminals and the subsequent policing practices performed by armed response officers to protect clients from this racially constructed dangerous ‘Other’. However, as the majority of armed response officers are ‘Bravo Mikes’ themselves, there is a constant element of friction in their performances. Based on 20 months of ethnographic fieldwork, this article thus analyses how racialised understandings of crime influence, and are reproduced by, private policing practices, thereby contributing to studies on private security occupational cultures and racial profiling.